Is music-with-movement intervention better than music listening and social activities in alleviating agitation of people with moderate dementia? A randomized controlled trial. (July 2020) - Cheung, Daphne Sze Ki; Lai, Claudia Kam Yuk; Wong, Frances Kam Yuet; Leung, Mason Chin Pang
Aim: Interactive music intervention is generally perceived as more effective on clinical outcomes than a receptive approach because it can better engage the people with dementia. The aim of this study is to compare the effects of the 6-week music-with-movement intervention on agitation of people with moderate dementia, music listening and social activity. Methods: A multi-centre randomized controlled trial was conducted on 165 nursing home residents with moderate dementia. The participants were randomly allocated into three groups: music-with-movement, music listening or social activities groups. Participants in the music-with-movement group listened to preferred music and moved their body parts for 45 minutes, twice a week for 6 weeks. While the participants in the music listening group only listened to their preferred music and social activity group chatted with the other group members. The agitation level was examined with the Chinese Cohen-Mansfield Agitation Inventory – Nursing Home version. Total scores and sub-scores (physically aggressive, physical non-aggressive, verbal aggressive and verbal non-aggressive) were compared at baseline, at post-intervention and 6 weeks post-intervention. Results: The results showed that there are no significant differences in agitation among three groups. Repeated measures univariate analyses revealed that all three groups yielded significant improvement in agitation from baseline to post-intervention, of which music-with-movement presented the largest effect size. Conclusion: This study showed that interactive or receptive type of music intervention or social activities may be helpful in managing agitation although there is no statistically significant difference among them.